Evaluation of special physical training of female students with different temperaments in aerobics - Inozemtseva E.S.; Guseva N.L.; Zemlyakova Z.S.; Cherepanova L.A. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to determination of differences in the parameters of special physical preparedness of female students with different types of temperament engaged in recreational aerobics. Methods and structure of the study. The pedagogical experiment was carried out from September to May 2024 on the basis of the Department of Physical Culture and Sports of the National Research Tomsk State University in Tomsk. Educational and training sessions on health-improving aerobics for female students of each subgroup, depending on the type of temperament, were conducted according to the work program of the discipline «Physical Education». The content, intensity, and duration of educational and training sessions (twice a week for two academic hours) were the same for female students of all temperament types. Results and conclusions. Differences in indicators of special physical preparedness of female students with different types of temperament were revealed. Significant intergroup differences (p≤0.05) were established in tests assessing endurance and dynamic balance. In the Karsh step test, which evaluates endurance, the best result was reliably (p≤0.05) recorded in phlegmatic people in comparison with melancholic people, sanguine people and choleric people. In the test for determining dynamic balance, the best result was established by choleric people (p≤0.05) in comparison with the group of sanguine and melancholic people. The obtained results of the study can be used in the educational and training process in physical education in educational institutions in order to improve the special physical fitness of those involved. Accordingly, taking into account temperament during recreational aerobics classes will make it possible to more effectively build the educational and training process in physical education, helping the trainer-teacher expand the components of an individual approach and determine methods of working with each student.